The effect of companies’ responses on their employer review platform rating - Soudil, Dominik Nicolas; Král, Petr, 1979-; Zachová, Daniela; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The aim of the bachelor thesis “The effect of companies’ responses on their employer review platform rating” is to identify whether there may be a link between employers’ replying to reviews on employer review platforms and receiving a better overall score on the same platforms. In the first part of the thesis, employer branding and its ties to employer review platforms are discussed first, followed by information about the platforms themselves. Furthermore, review of current evidence on replying to reviews on various online platforms was conducted. In the second and practical part of the thesis, research was carried out, focusing on the correlation between responding and gaining higher score. The second part also includes explanation of the methodology used, results and discussion, conclusion with recommendations, managerial implications and limitations of the thesis. The thesis was written in the hope of aiding businesses with decisions in the realms of employer review platforms.
Vedoucí práce: Petr Král
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses